2018
DOI: 10.1111/ijfs.14027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amino acids on Maillard reaction product formation and total antioxidant capacity in white pan bread

Abstract: Maillard reaction products (MRPs) can be an important dietary antioxidant source. Bread is the most popular bakery product; however, limited information is available on the antioxidant activities of MRPs generated during bread-baking. This paper reports the effect of different amino acids on bread properties, melanoidin formation and antioxidant activities. Totally six amino acids at four different levels were evaluated. Increasing the amount of amino acid led to darker bread crust, higher melanoidin content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…Differences in yellow tonality, although not as pronounced, were found between common bread and the other two products, where soft bread and biscuits had higher b* values than common bread (Figure 1C). It is noteworthy that factors such as amino acid and sugar composition, that are critical ingredients in bakery products, could contribute to crust browning (Shen, Chen, Li & Tebben, 2019).…”
Section: Cielab Colour Space Analysis Of the Food Matrices Crustmentioning
confidence: 99%
“…Differences in yellow tonality, although not as pronounced, were found between common bread and the other two products, where soft bread and biscuits had higher b* values than common bread (Figure 1C). It is noteworthy that factors such as amino acid and sugar composition, that are critical ingredients in bakery products, could contribute to crust browning (Shen, Chen, Li & Tebben, 2019).…”
Section: Cielab Colour Space Analysis Of the Food Matrices Crustmentioning
confidence: 99%
“…The addition of asparagine into the bread dramatically increased the acrylamide content, as expected, while the addition of glycine and proline significantly decreased acrylamide content. Considering our previous study (Shen, Chen, et al, ; Shen, Tebben, et al, ), the bread formulas with additional ribose, proline, and glycine‐enhanced bread's antioxidant activity while decreasing acrylamide formation.…”
Section: Discussionmentioning
confidence: 73%
“…Melanoidins in biscuits showed potential antioxidant activity in the protection of human HepG2 cells against oxidation as well as strong metal chelating activity and anti‐inflammatory activity as determined in in vitro studies (Bekedam, Roos, Schols, Boekel, & Smit, ; Helou et al, ; Martín et al, ). In our previous study, we reported that the increased amount of sugars and amino acids all favored the Maillard reaction and improved the antioxidant capacity of bread (Shen, Chen, & Li, ; Shen, Tebben, Chen, & Li, ). However, the Maillard reaction also generates many toxic compounds, such as acrylamide, 5‐hydroxymethylfurfural, and other advanced glycation end‐products, also known as glycotoxins, associated with reduced availability of essential amino acids, tissue damage, and degenerative disorders (Bastos, Monaro, Siguemoto, & Séfora, ; Delgado‐Andrade, ).…”
Section: Introductionmentioning
confidence: 99%
“…In many studies investigating the nonenzymatic browning reactions in model systems, it was shown that the lysine is the most reactive amino acid (Ajandouz & Puigserver, 1999; Ashoor & Zent, 1984; Hemmler et al., 2018). Shen, Tebben, Chen, and Li (2018) studied on the effects of different amino acids on bread properties and reported that breads with darker and less yellowish crust colors were obtained with the addition of amino acids. In this study, breads made with lactose and whey enriched doughs leavened by K. lactis had lower color change when compared to the ones leavened by S. cerevisiae , however, the difference was not found to be statistically significant for whey added formulation.…”
Section: Resultsmentioning
confidence: 99%